Sensation in Gamification: A Qualitative Investigation of Background Music in Gamified Learning - Freitas, José Alexandre de; Oliveira, Mateus; Martinelli, Carlos; Amorim, Fernando; Toda, Armando M.; Palomino, Paula; Klock, Ana C. T.; Guerino, Guilherme; Avila-Santos, Anderson P.; Rodrigues, Luiz (Journal on Interactive Systems, 2024)
Gamification in education has received significant attention for its potential to enhance student engagement and motivation. However, challenges arise from the excessive use of reward-oriented game elements, which are assumed to have negative effects on learning outcomes in many cases. In contrast, while the literature argues immersion-based gamification holds great potential, there is little research on how such an approach affects learning experiences. The Sensation game element, for instance, might contribute to students' experiences by providing sensory queues, such as auditory feedback based on background music, to foster concentration, engagement, and immersive learning experiences. Nevertheless, past studies have not sufficiently investigated how the Sensation game element affects gamified learning experiences. Therefore, this paper implements the Sensation game element in two studies: Study 1 introduced background music during a reading activity, while Study 2 implemented multiple background music tracks aligned with different learning stages to drive students' experiences. Accordingly, we evaluated this game element through usability tests, based on high-fidelity prototypes of online learning environments, followed by semi-structured interviews that were analyzed through thematic analysis with the help of ChatGPT. Overall, we found that Sensation, particularly instrumental music, positively influenced concentration but requires careful design to maintain engagement. The findings highlight the importance of tailoring Sensation's implementation to consider individual preferences and contextual factors and the need for thoughtful selection and management of sensory queues to optimize learning environments effectively. Additionally, we provide evidence emphasizing the value of using tools like ChatGPT to optimize qualitative data analysis, although human oversight remains prominent to ensure robust research outcomes. Overall, this study contributes insights for designing personalized and effective gamified learning experiences based on the Sensation game element in enhancing learning experiences.